Research on the Development of CPA Audit from the Perspective of Artificial Intelligence - Zhou Guangxiu (E3S Web of Conferences, 2021)
In the context of the continuous development of Internet technology, big data, Internet of things, cloud computing and other technologies have developed rapidly, and artificial intelligence technology has emerged as the times require. The development of new technologies has promoted social change. As soon as artificial intelligence technology is put forward, it has been widely concerned by the society. Artificial intelligence is like a double-edged sword. As an emerging technology, it is constantly influencing all walks of life, and its application in the field of audit has become the general trend. Under the Background of the rise of artificial intelligence, this paper puts forward the advantages of the combination of artificial intelligence and audit, and analyzes the challenges faced by the development of CPA audit industry, seize the opportunity of the times, actively apply artificial intelligence technology, give practical suggestions for the long-term development of the audit industry, in order to improve the audit efficiency and ensure the audit effect.